210Pb and 7Be as Coupled Flux and Source Tracers for Aerosols in the Pacific Ocean. Issue 8 (11th August 2022) - Wei, Ziran; Cochran, J. Kirk; Horowitz, Evan; Fitzgerald, Patrick; Heilbrun, Christina; Kadko, David; Stephens, Mark; Marsay, Chris M.; Buck, Clifton S.; Landing, William M.
Abstract: Deposition of aerosols to the surface ocean is an important factor affecting primary production in the surface ocean. However, the sources and fluxes of aerosols and associated trace elements remain poorly defined. Aerosol 210 Pb, 210 Po, and 7 Be data were collected on US GEOTRACES cruise GP15 (Pacific Meridional Transect, 152°W; 2018). 210 Pb fluxes are low close to the Alaskan margin, increase to a maximum at ∼43°N, then decrease to lower values. There is good agreement between 210 Pb fluxes and long‐term land‐based fluxes during the SEAREX program (1970–1980s), as well as between GP15 and GP16 (East Pacific Zonal Transect, 12°S; 2013) at adjacent stations. A normalized fraction f ( 7 Be, 210 Pb) is used to discern aerosols with upper (high f ) versus lower (low f ) troposphere sources. Alaskan/North Pacific aerosols show significant continental influence while equatorial/South Pacific aerosols are supplied to the marine boundary layer from the upper troposphere. Lithogenic trace elements Al and Ti show inverse correlations with f ( 7 Be, 210 Pb), supporting a continental boundary layer provenance while anthropogenic Pb shows no clear relationship with f ( 7 Be, 210 Pb). All but four samples have 210 Po/ 210 Pb activity ratios <0.2 suggesting short aerosol residence time. Among the four samples ( 210 Po/ 210 Pb = 0.42–0.88), two suggest an upper troposphere source and longer aerosol residence time while the remaining two cannot be explained by long aerosol residence time nor a significant component of dust. We hypothesize that enrichments of 210 Po in them are linked to Po enrichments in the sea surface microlayer, possibly through Po speciation as a dissolved organic or dimethyl polonide species. Key Points: North Pacific aerosols are influenced by continental sources while South Pacific aerosols have upper troposphere sources 7 Be/ 210 Pb shows that Al, Ti, and Fe have continental‐influenced lower troposphere sources; Pb has lower‐ and upper troposphere sources Elevated aerosol 210 Po/ 210 Pb may indicate addition of Po from the sea surface as an organic Po or dimethyl polonide species